1985
DOI: 10.1111/j.1440-1827.1985.tb00615.x
|View full text |Cite
|
Sign up to set email alerts
|

An Immunofluorescent Study of Generalized Coxsackie Virus B3 Infection in a Newborn Infant

Abstract: An autopsy case of a 10‐day‐old newborn with generalized infection of Coxsackie virus B3 (CBV3) was reported. CBV3 was isolated from the blood before death. The patient died of cardiac failure. An immunofluorescent study was carried out on autopsy specimens fixed in formalin and embedded in paraffin. CBV3 antigen was detected in the heart, brain, kidney, lungs, spleen, thymus, and pancreas. In the pancreas CBV3 antigen was predominantly seen in the islet cells. No CBV3 antigen was found in the liver and adrena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…Regardless, there are numerous publications that suggest a large amount of damage is inflicted by the virus itself, in the murine model, early post-infection, that is correlated with the number of myocarditic lesions spatially coincident with positivity by in situ hybridization for CVB3 genome (Cheung et al, 2008;Chow et al, 1992;Marchant et al, 2009a;McManus et al, 1993). These observations are supported by findings in autopsy cases, particularly in infants (Iwasaki et al, 1985a;Iwasaki et al, 1985b).…”
Section: Viral Replication As the Central Regulator Of Viral Myocarditissupporting
confidence: 72%
“…Regardless, there are numerous publications that suggest a large amount of damage is inflicted by the virus itself, in the murine model, early post-infection, that is correlated with the number of myocarditic lesions spatially coincident with positivity by in situ hybridization for CVB3 genome (Cheung et al, 2008;Chow et al, 1992;Marchant et al, 2009a;McManus et al, 1993). These observations are supported by findings in autopsy cases, particularly in infants (Iwasaki et al, 1985a;Iwasaki et al, 1985b).…”
Section: Viral Replication As the Central Regulator Of Viral Myocarditissupporting
confidence: 72%
“…A predisposing, multigenic component has been described but accounts for fewer than 50% of cases (7,35,45); environmental factors (e.g., viral infections) have therefore been proposed to explain the remaining cases of T1D (3,6,32,57,58) that cannot be ascribed solely to host-driven pathogenic autoimmunity. Human enterovirus (HEV) infections have long been suspected as environmental triggers of human T1D (12,22,27); infections by common HEVs, such as the group B coxsackieviruses (CVB 1 to 6) and diverse echoviruses, have been implicated as triggers of T1D onset at the time of or shortly after infection (8,9,13,19,28,37,39,40,42,52,60). Nonetheless, it remains unclear whether HEV initiates T1D in humans (18,21,24,26); evidence supporting an etiologic connection between HEV infection and T1D onset is not as well-established as the links between, for example, specific HEV infections and poliomyelitis, aseptic meningitis, or myocarditis (43).…”
mentioning
confidence: 99%
“…Vertical transmission of CV-B associated with foetal thymus infection has been reported [Iwasaki et al, 1985;Lozovskaia et al, 1997]. In addition, it has been shown that enterovirus infections in utero may induce b-cell autoimmunity [Otonkoski et al, 2000], and that CV-B4 infection during pregnancy was a risk factor for childhood-onset type 1 diabetes [Dahlquist et al, 1995;Hyöty et al, 1995].…”
Section: Introductionmentioning
confidence: 97%